DESAIN PEMBELAJARAN PAI DALAM IMPLEMENTASI KURIKULUM MERDEKA DI SD IT MUTIARA HATI RIMBO BUJANG. - Swasono Adhi, Bangun; Mualimin; Adilla, Ulfa; Mabruri; Supran Titis Ishaq, Maula (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the constraints and solutions in the design of Islamic Religious Education (PAI) learning during the implementation of the Merdeka Curriculum at SD IT Mutiara Hati.This research utilized a qualitative approach with a descriptive method, conducted through interviews, observations, and documentation involving PAI teachers and relevant parties. The research findings indicate that the primary constraints faced include teachers' limited understanding of the Merdeka Curriculum concept, the scarcity of contextual learning resources, and students' low motivation in project-based activities.The solutions implemented include continuous teacher training, the development of innovative media and teaching materials, and the application of project-based learning (PjBL) models that foster religious values and students' character. Thus, an adaptive and creative PAI learning design is the key to the successful implementation of the Merdeka Curriculum in the integrated Islamic school environment.